Blockchain technologies in agricultural sector transformation: ESG-oriented public management model for post-war recovery - Babaiev, Valerii; Kravchenko, Oleksandr (Pressing Problems of Public Administration, 2025)
This article explores the potential of integrating blockchain technologies into public management of Ukraine’s agricultural sector for post-war recovery through the lens of ESG principles. The authors analyze limitations of traditional regulatory models, particularly information asymmetry, lack of transparency in state support distribution, and limited access to financing for small and medium agricultural producers. The proposed concept envisions transforming state institutions from monopolistic regulators into infrastructural participants of network partnerships. The research reveals significant shortcomings in existing financing mechanisms, where approximately 75% of small agricultural enterprises face loan rejections, while traditional international payment instruments are characterized by high costs and low efficiency. The authors propose implementing agricultural asset tokenization mechanisms based on distributed ledger technology, enabling transparent, automated, and inclusive mechanisms for state support and private financing. A comparative analysis of traditional and innovative blockchain-based public management models is developed according to criteria of transparency, trust-building mechanisms, operational efficiency, and adaptability to ESG requirements. The study examines mechanisms for tokenizing agricultural assets with integrated ESG parameters, ensuring programmable responsibility of producers for compliance with environmental, social, and governance standards. Methods for implementing ESG standards are presented through: tokenization of ESG obligations, decentralized ESG certification, and programmed ESG regulation. Practical implementation of the proposed instruments is illustrated using examples of a decentralized blockchain platform for pre-ordering food poppy products and carp farming. The authors demonstrate that integrating distributed ledger technology creates conditions for democratizing market access, supply chain transparency, and automated verification of ESG criteria compliance, transforming them from regulatory requirements into competitive advantages. Implementing the proposed model requires not only technological modernization but also institutional transformation of regulatory bodies and development of specialized digital inclusion programs to bridge the digital divide in rural areas.